The Role of Artificial Intelligence in Eliminating Language and Cultural Barriers in Cross-Border E-commerce - Keser, Hilal Yildirir (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Cross-border e-commerce allows businesses to access international markets but faces significant language and cultural barriers. This study examines how artificial intelligence technologies overcome these challenges. Through literature review and case analyses, the study identifies major language barriers including translation quality and content creation, and cultural barriers such as design preferences and payment methods. The research demonstrates how AI applications like neural machine translation, culturally responsive recommendation systems, and AI-powered chatbots effectively address these challenges. Case studies for global platforms (Amazon, Alibaba, eBay) and SMEs reveal that the implementation of AI solutions has significantly increased international sales, dramatically improved translation accuracy and increased customer engagement. The findings suggest businesses should integrate AI into their internationalization strategies while maintaining human oversight and cultural sensitivity. This study contributes to understanding how AI transforms cross-border e-commerce by eliminating traditional barriers to global market entry.